Food Estate: Problem Solving or Destruction? Netnography Approaches Using Network Analysis Through Youtube Channel BBC News Indonesia - Abadi, Medi Trilaksono Dwi (Jurnal Paradigma, 2025)
This research focuses on netnographic studies using a social network analysis approach related to the Food Estate program in Gunung Mas, Central Kalimantan. The research location is the BBC News Indonesia YouTube channel with the video content research object entitled Food Estate: Forests are gone, thousands of hectares of gardens and rice fields have failed to harvest - BBC News Indonesia which was uploaded March 15, 2023 with the unique video code Zv_6jPUDAM4&t=63s. This research is research with secondary data. The results of the research show that according to netizens' responses, the food estate program is considered a failed program, even since 1970 the era of "rice estate" has only now been replaced by the name "food estate". Netizens responded via the comments column with a variety of positive and negative tones.